Engineering wireless mesh networks : joint scheduling, routing, power control, and rate adaptation - Luo, Jun (2014)
We present a number of significant engineering insights on what makes a good configuration for medium- to large-size wireless mesh networks (WMNs) when the objective function is to maximize the minimum throughput among all flows. For this, we first develop efficient and exact computational tools using column generation with greedy pricing that allow us to compute exact solutions for networks significantly larger than what has been possible so far. We also develop very fast approximations that compute nearly optimal solutions for even larger cases. Finally, we adapt our tools to the case of proportional fairness and show that the engineering insights are very similar.